Social expectations towards a kindergarten’s teacher – statement of research - Leżańska, Wiesława; Feliniak, Aleksandra; Agnieszka Gralak (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
This article consists an attemption to do an analysis of the present-day expectations towards the teachers in polish kindergartens. The position of the role of the kindergarten’s teacher had been presented in a wider context of social transformations in Poland. A separate part of this article is a characterization of meaning and value of the proper partnership in the parent-teacher paradigm, well as highlighting the problems and benefits related to this partnership.